IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 14 TAHUN 2011 TENTANG RENCANA TATA RUANG WILAYAH KOTA SEMARANG 2011-2031 (Studi Kasus Penataan Ruang Kawasan Simongan) - Hamidah Kurniawati; Aloysius Rengga (Journal of Public Policy and Management Review, 2016)
Landscaping area is the process of spatial planning and space utilization to control the development of the region. Spatial planning Semarang itself is set in Semarang City Regional Regulation No. 14 of 2011 on Spatial Planning Semarang City Year 2011-2031. Implementation of these regulations is difficult to do, as it happens in Simongan Region, District of West Semarang. Simongan region is mentioned as a settlement area of allotment, the trade and services and not as an industrial area. But in fact there are 12 companies located in the region. There is resistance from employers, factory workers and the public against this policy because the policy had an impact on the social and economic fields. Hampered by the problem of financial resources. However Semarang City Government still taking action to not issue a business license for industry in Region Simongan industry for entrepreneurs willing to relocate. There are several factors that affect the implementation of this policy, the resources, the strategy of implementing actors, characteristics of institutions and authorities, public response and target groups as well as compliance with the target group. It should be done reexamining the region by involving community, business, academia and experts structuring policy space in order to be accepted by all parties and in accordance with the existing problems at the site.